2005
DOI: 10.1042/bj20042064
|View full text |Cite
|
Sign up to set email alerts
|

Residue 234 in glutathione transferase T1-1 plays a pivotal role in the catalytic activity and the selectivity against alternative substrates

Abstract: GST (glutathione transferase) T1-1 plays an important role in the biotransformation of halogenated alkanes, which are used in large quantities as solvents and occur as environmental pollutants. Many reactions that are catalysed by GST T1-1 qualify as detoxification processes, but some reactions with dihalogenated alkanes lead to reactive products more toxic than the substrates. Murine GST T1-1 is particularly active with dichloromethane, which may explain the high carcinogenicity of dichloromethane in the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 34 publications
1
36
0
1
Order By: Relevance
“…The epoxide EPNP, the alkylhalide iodomethane, and NPB have often been regarded as signature substrates of GST T1-1 (16,21). Indeed, the R234W activities with these substrates were still the highest in absolute numbers but just Ͻ3% of the wild type values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The epoxide EPNP, the alkylhalide iodomethane, and NPB have often been regarded as signature substrates of GST T1-1 (16,21). Indeed, the R234W activities with these substrates were still the highest in absolute numbers but just Ͻ3% of the wild type values.…”
Section: Resultsmentioning
confidence: 99%
“…In position 234, the human enzyme has Trp, whereas the mouse enzyme has Arg. We have previously shown that mutation of Trp into Arg in the human enzyme induces significant elevation of catalytic activity with a number of substrates (16). To test if the reverse mutation, Arg to Trp, in a homologous enzyme is sufficient to suppress catalytic activities, this substitution was introduced in mouse GST T1-1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3C). SCR23 also contained two point mutations, L113P and W234R, the latter of which is known to play a role in substrate selectivity (28). It is noteworthy that SCR23 contains a lowhomology C͞O near the middle of the electrophile-determining H site, indicating that exchange of parental C-terminal subdomains can give rise to enzymes with high catalytic activity.…”
Section: Resultsmentioning
confidence: 99%